Effect of Performance-Based Remuneration and Organizational Support on Clinical Pathway Compliance - Eko Wahyu Irvan Saputro; Duta Liana; Yanuar Ramadhan (Global Management: International Journal of Management Science and Entrepreneurship, 2026)
Compliance with clinical pathways is a critical component in ensuring quality of care, patient safety, and cost efficiency in hospitals. However, its implementation continues to face challenges related to management systems and the work behavior of Healthcare Providers (HCPs). This study aimed to analyze the effect of performance-based remuneration systems and organizational support on clinical pathway compliance, with work discipline serving as an intervening variable among HCPs at Cabangbungin Regional General Hospital.This research employed a quantitative approach with an explanatory research design. Data were collected using structured questionnaires and analyzed through Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) approach, supported by the three-box method analysis. The findings indicate that performance-based remuneration systems and work discipline have a significant positive effect on clinical pathway compliance. Furthermore, work discipline was found to strengthen the relationship between performance-based remuneration and compliance, confirming its mediating role. In contrast, organizational support did not show a significant direct or indirect effect on clinical pathway compliance.The study concludes that compliance with clinical pathways is more strongly influenced by performance control mechanisms and clinical work discipline than by general organizational support. These findings provide evidence-based insights for hospital management in designing sustainable strategies and policies to enhance clinical pathway adherence and improve service quality.